Role of pattern, regularity, and silent intervals in auditory stream segregation based on inter-aural time differences - Carl, David; Gutschalk, Alexander (Experimental brain research, 2013)
Tone triplets separated by a pause (ABA_) are a popular tone-repetition pattern to study auditory stream segregation. Such triplets produce a galloping rhythm when integrated, but isochronous rhythms when segregated. Other patterns lacking a pause may produce less-prominent rhythmic differences but stronger streaming. Here, we evaluated whether this difference is readily explained by the presence of the pause and potentially associated with the reduction of adaptation, or whether there is contribution of tone pattern per se. Sequences with repetitive ABA_ and ABAA patterns were presented in magnetoencephalography. A and B tones were separated by differences in inter-aural time differences (ΔITD). Results showed that the stronger streaming of ABAA was associated with a more prominent release from the adaptation of the P1m in auditory cortex. We further compared behavioral streaming responses for patterns with and without pauses, and varied the position of the pause and pattern regularity. Results showed a major effect of the pauses’ presence, but no prominent effects of tone pattern or pattern regularity. These results make a case for the existence of an early, primitive streaming mechanism that does not require an analysis of the tone pattern at later stages suggested by predictive-coding models of auditory streaming. The results are better explained by the simpler population-separation model and stress the previously observed role of neural adaptation for streaming perception.